Cultivating Sustainable Futures: Investigating the Interplay of Agriculture, Climate Change Resilience, and Food Security in Vulnerable Regions - Kameda Karki Qiu; Pritchard Pritchard; Hansen Mbow; Dovers Szenderák MJ; Brasz Dull (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2021)
This research delves into the intricate web of challenges facing vulnerable regions, focusing on the dynamic interplay of agriculture, climate change resilience, and food security. Vulnerable regions, often characterized by poverty and limited resources, are disproportionately affected by climate change and food insecurity. Through a comprehensive investigation that integrates qualitative and quantitative data, this study unveils critical insights. The research underscores the undeniable interconnectedness of these dimensions. Changes in agricultural practices have profound implications for food security, while climate variability directly impacts crop yields. Contextual factors, including geography, culture, and socioeconomic conditions, shape the unique vulnerabilities of each region. Smallholder farmers emerge as central actors, holding invaluable local knowledge and adaptive strategies that underpin resilience. Gender and intersectionality play pivotal roles in shaping vulnerabilities, demanding gender-sensitive approaches and holistic understanding. The temporal dimension is emphasized, highlighting the importance of sustainability in interventions. Community engagement and ownership emerge as cornerstones of effective resilience-building, underscoring the need for participatory approaches. The findings of this research are of profound significance for policy, practice, and future research. They call for tailored, context-specific solutions that recognize the agency and resilience of local communities. Smallholder farmers and women must be central in the journey toward resilience, and sustainability must be a guiding principle. Community-led initiatives rooted in local contexts and needs offer a pathway forward. This research contributes to addressing pressing global issues, including poverty alleviation, climate change mitigation, and sustainable development. It offers a roadmap for more resilient, sustainable, and equitable futures for vulnerable communities worldwide, emphasizing the transformative power of context-specific, community-centered approaches.